The Temporal Rhythm of Alcohol Consumption: On the Development of Young People's Weekly Drinking Patterns. (June 2019) - Andrade, Stefan B.
This article investigates young people's weekly drinking patterns during late adolescence and young adulthood. The article builds a disaggregated and temporal framework to explain how young people drink on certain days. Using sequence analysis techniques on longitudinal data from a representative Danish survey, the article identifies four drinking patterns (the majority, the weekend drinkers, the weekend bingers and the heavy drinkers). Analyses of the transitions between the drinking patterns reveal non-linear developments where heavy drinking at an early age does not necessarily lead to heavy drinking later in life. Although parental income and education are important factors to explain whether young people begin to drink at an early age, high levels of alcohol consumption during youth is more associated with influenced from peers and partners.